Gendered Strategies between Democratization and Democratic Reversal: The Curious Case of Turkey - Aksoy, Hürcan Asli (2018)
The processes of democratization or democratic reversal have serious implications for gender equality regimes. Although the gender and transition literature has extensively examined the relation between democratization and gender, it only recently began to question how the changing dynamics of democratic reversal influence gender politics and policies. While women’s participation and representation in the formal arena of politics has been the primary object of theoretical discussions, the research rediscovers the power of the informal arena. To find tentative answers to the newly developing research agenda, this article employs the case of Turkey. To this end, the article examines the gendered strategies of four groups of organized women (feminist, Kurdish, Islamist, and Kemalist women’s organizations) engaged in strengthening women’s rights and gender equality. It first questions how, and to what extent, organized women engendered democratization process and then sheds lights on the shift in their strategies to respond to the increasingly authoritarian and conservative Islamist political agenda of the ruling Justice and Development Party. Drawing on empirical findings, the article aims to inform the theoretical debates on the analytical relation between democratic reversals and gender rights regimes.